Performativna snaga imena u zbirci priča „Inšallah Madona, inšallah” Miljenka Jergovića - Lujanović, Nebojša (Wydawnictwo Naukowe UAM, 2013)
The names play a main role in understanding of Miljenko Jergović’s literary works and it is argued through analysis of collection of stories called Inšallah Madona, inšallah. The names have their history, they describe and determine actors, and function as axioms with initial stabile meaning. By decoding of related code, new complex components of semantic field of the name as symbol are revealed to us. In chosen text, the names operate as curse in form of general principle. Through curse as a main motive, it is implied performative dimension of the names which symbolize pain or misery, evoke tragedy and in the end fulfil inscribed curse.
The Performative Potential of Names in Miljenko Jergović’s Collection of Stories "Inšallah Madona, inšallah"
Keywords: name; symbol; code; decoding; curse; performative